Pengaruh Pemberian Udang Ebi Dengan Konsentrasi Yang Berbeda Terhadap Pertumbuhan Tukik Penyu Lekang (Lepidochelys olivacea) Di Pantai Samas, Bantul - Hardiono, Bagus Eko; Redjeki, Sri; Wibowo, Edi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Turtle is an organism that spends his life at sea and be able to migrate long distances along the Indian Ocean, Pacific Ocean and Southeast Asia. The presence of turtles in Indonesia are increasingly threatened with extinction, both natural and human activities that lead to the existence of the endangered sea turtles. The purpose of this study was to determine the effect of giving different feed concentrations on the growth of hatcling olive ridley turtle (Lepidochelys olivacea) The age of 2 weeks during the treatment period of 10 weeks. Data is collected from 21 August to 30 October 2010 using the experimental method. The study was conducted at Samas beach Yogyakarta. Feed given in the form of shrimp ebi 3% and 8% of the weight of biomass. The number of hatchlings that are used are 12 tails that are placed in six containers. Measurement of growth of weight, length and width of hatchlings carried out once every 2 weeks for 10 weeks of observation. The results of the study indicate that the hatchlings fed shrimp ebi with a concentration of 3% have a specific growth rate on average 0366 Â± 0008 is smaller than hatchlings fed with a concentration of 8% on average 0425 Â± 0006. The results of data analysis using the specific growth rate of the test statistic t with feeding treatment with different concentrations showed that the sig. (2-tailed) = 0.000 or p <0.05. So it can be proved that the specific growth rate in both treatments were significantly different.